PREDICTION OF THE PRODUCTIVE PERFORMANCE OF GUINEA PIECES THROUGH THE USE OF PHYTOBIOTICS - Timana Sandoval, Manuel Augusto (2025)
The present research seeks to evaluate the use of a phytobiotic in the fattening phase of guinea pigs (Cavia porcellus) by predicting its impact on weight gain, feed consumption and feed conversion. A predictive model based on linear regression was developed to estimate the benefits of the phytobiotic. The guinea pigs that received the supplement showed a significant weight increase (1040.30 g compared to 967 g in the control group), as well as an improvement in feed conversion. This study suggests that the use of phytobiotics is a viable alternative to antibiotics, improving both productive efficiency and sustainability in guinea pig farming.